Kajian Hukum Terhadap Perlindungan Hak Investor Dalam Transaksi Pasar Modal - Dehan Fahresta; Farhan Adry Pratama; Ridho Ammatullah; Helfira Citra (GLOBAL SCIENTS PUBLISHER, 2024)
The capital market is one of the key instruments in Indonesia’s economy, facilitating companies to raise capital and offering investment opportunities to the public. However, the increasingly complex nature of transactions in the capital market also presents risks that may harm investors. One of the main issues is the lack of adequate protection for investors, which can lead to substantial financial losses. This study aims to examine and analyze the legal protection of investor rights in capital market transactions in Indonesia, focusing on the effectiveness of existing regulations. The primary legal framework includes Law No. 8 of 1995 on Capital Markets and regulations issued by the Financial Services Authority (OJK) and the Indonesia Stock Exchange (IDX). This research adopts a normative juridical method with a descriptive-analytical approach. The findings suggest that despite the presence of clear regulations, challenges such as suboptimal supervision, a lack of investor legal literacy, and slow law enforcement hinder effective protection. Therefore, enhancing supervision and providing investor education are necessary to optimize investor protection.